Redox-Responsive Drug Delivery Systems: A Chemical Perspective - Abed, Heba (2022)
With the widespread global impact of cancer on humans and the extensive side effects associated with current cancer treatments, a novel, effective, and safe treatment is needed. Redoxresponsive drug delivery systems (DDSs) have emerged as a potential cancer treatment with minimal side effects and enhanced site-specific targeted delivery. This paper explores the physiological and biochemical nature of tumors that allow for redox-responsive drug delivery systems and reviews recent advances in the chemical composition and design of such systems. The five main redoxresponsive chemical entities that are the focus of this paper are disulfide bonds, diselenide bonds, succinimide–thioether linkages, tetrasulfide bonds, and platin conjugates. Moreover, as disulfide bonds are the most commonly used entities, the review explored disulfide-containing liposomes, polymeric micelles, and nanogels. While various systems have been devised, further research is needed to advance redox-responsive drug delivery systems for cancer treatment clinical applications.